Karakteristik Kimia dan Sensori Crispy Cookies Kacang Hijau (Vigna radiata) dengan Penambahan Tepung Pisang Susu (Musa acuminata var. Silk) - Puteri Anggrayni; Maria Marina Herawati (JURNAL AGROINDUSTRI HALAL, 2025)
Crispy cookies are processed pastries that are usually made from wheat flour. Flour in making crispy cookies can use other alternatives, namely local food-based flour such as mung bean flour and milk banana flour. The researcher aims to determine the chemical and sensory characteristics and obtain the best treatments according to chemical analysis (analysis of water, carbohydrate, protein, ash, and fat content, E.coli contamination,) and organoleptic tests. This research used a Randomized Block Design (RAK) including 5 treatments and 5 replications. The five treatments had the following ratio of green bean flour to milk banana flour, P0 (100% : 0%), P1 (90%: 10%), P2 (80%: 20%), P3 (70%: 30%), and P4 (60%: 40%). Addition of milk banana flour has a significant effect on increasing water content, but does not have a substantial effect on protein, ash, fat, and carbohydrat content. The best treatment according to chemical analysis and organoleptic tests is P2 treatment.